2009
DOI: 10.1029/2009gc002561
|View full text |Cite
|
Sign up to set email alerts
|

Seismic tremor at the 9°50′N East Pacific Rise eruption site

Abstract: [1] Ocean bottom seismic observations within the 9°50 0 N region of the East Pacific Rise indicate persistent, low-amplitude tremor activity throughout the October 2003 through February 2007 period of monitoring. These signals exhibit either monochromatic or polychromatic spectral characteristics, with a $6 Hz fundamental frequency and up to two harmonics. Individual events cannot be correlated between nearby (<1 km) stations, implying the presence of multiple, small-amplitude sources positioned within the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Occurrence of harmonic tremors similar to those observed in this work has been reported in other volcanic and non-volcanic regions of the world, e.g., Pontoise and Hello (2002) offshore Ecuador, Tolstoy et al (2002) near Axial volcano on the Juan de Fuca Ridge, Díaz et al (2007) at the Galicia Margin, Monigle et al (2009) at the 9º50' East Pacific Rise, Bazin et al (2010) in Guadeloupe, French West Indies, and Franek et al (2014) in the SW Barents Sea margin. Several hypotheses have been proposed, as discussed later, to explain their origin.…”
Section: Harmonic Tremorsupporting
confidence: 87%
See 1 more Smart Citation
“…Occurrence of harmonic tremors similar to those observed in this work has been reported in other volcanic and non-volcanic regions of the world, e.g., Pontoise and Hello (2002) offshore Ecuador, Tolstoy et al (2002) near Axial volcano on the Juan de Fuca Ridge, Díaz et al (2007) at the Galicia Margin, Monigle et al (2009) at the 9º50' East Pacific Rise, Bazin et al (2010) in Guadeloupe, French West Indies, and Franek et al (2014) in the SW Barents Sea margin. Several hypotheses have been proposed, as discussed later, to explain their origin.…”
Section: Harmonic Tremorsupporting
confidence: 87%
“…The harmonic tremors reported in other regions (e.g., Pontoise and Hello, 2002;Tolstoy et al, 2002;Díaz et al, 2007;Monigle et al, 2009;Bazin et al, 2010;Franek et al, 2014) have been associated with gas venting and/or resonance of fluid-filled cracks. The geological setting of the Canary Channel would support an interpretation of the harmonic tremors in terms of resonant vibrations associated with gas seepage.…”
Section: Harmonic Tremormentioning
confidence: 97%
“…Tidally modulated tremor has been found at other hydrothermal systems. Monigle et al () found comparable harmonic tremor at OBS on the East Pacific Rise that was attributed to hydrothermal flow in cracks close to the OBS. There, too, tremor pattern changed in connection with a magmatic event.…”
Section: Discussionmentioning
confidence: 94%
“…Ocean-bottom seismometers (OBSs) are usually deployed in marine settings to investigate local seismicity of an area by monitoring earthquakes (e.g., Grevemeyer et al, 2015;Meier et al, 2021) or long-duration tremors (e.g., Monigle et al, 2009;Hsu et al, 2013;Franek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%